STRATEGI PEMBELAJARAN DALAM MENGATASI KRISIS ATENSI PESERTA DIDIK DI ERA DIGITAL - Luana Sasabone; Anggun Wida Prawira; Vindi Tyastutik; Arini Zulfaida (LPPM Universitas Nias Raya, 2026)
This study was motivated by the growing concern over students’ attention deficits in the digital era, which have been exacerbated by the pervasive presence of technological distractions during learning activities. Devices such as smartphones, tablets, and constant access to social media platforms create competing stimuli that fragment students’ focus, reduce engagement, and limit their capacity to process and retain information effectively. In response to this issue, the study aimed to identify and synthesize effective learning strategies that can mitigate attention crises and enhance the quality of learning in digitally saturated environments. To achieve this objective, the research employed a Systematic Literature Review (SLR) method. Journal articles were systematically retrieved from reputable databases, including Google Scholar, ERIC, and Garuda, ensuring a comprehensive and credible selection of literature. The research instrument consisted of article documentation sheets, which facilitated consistent data extraction and comparison. Articles were carefully screened and selected based on predetermined inclusion and exclusion criteria to maintain relevance and reliability. The collected data were then subjected to thematic analysis, allowing the classification of learning strategies according to their effectiveness in promoting students’ attention and engagement. The findings indicate that active learning strategies, structured management of digital distractions, and activity-based learning models are particularly effective in enhancing students’ focus during learning sessions. These approaches encourage meaningful participation, sustain engagement, and promote self-regulation among learners. Accordingly, teachers are advised to design interactive, technology-mediated learning experiences that are structured and intentional, enabling students to overcome attention challenges while fostering deeper understanding and long-term retention of knowledge.